Inflammation Enhances the Risks of Stroke and Death in Chronic Chagas Disease Patients. - Paulo Marcos Matta Guedes; Cléber Mesquita de Andrade; Daniela Ferreira Nunes; Nathalie de Sena Pereira; Tamyres Bernadete Dantas Queiroga; George Luiz Lins Machado-Coelho; Manuela Sales Lima Nascimento; Maria Adelaide Do-; Antônia Cláudia Jácome da Câmara; Egler Chiari; Lúcia Maria da Cunha Galvão (Public Library of Science (PLoS), 2016)
Ischemic strokes have been implicated as a cause of death in Chagas disease patients. Inflammation has been recognized as a key component in all ischemic processes, including the intravascular events triggered by vessel interruption, brain damage and repair. In this study, we evaluated the association between inflammatory markers and the death risk (DR) and stroke risk (SR) of patients with different clinical forms of chronic Chagas disease. The mRNA expression levels of cytokines, transcription factors expressed in the adaptive immune response (Th1, Th2, Th9, Th17, Th22 and regulatory T cell), and iNOS were analyzed by real-time PCR in peripheral blood mononuclear cells of chagasic patients who exhibited the indeterminate, cardiac, digestive and cardiodigestive clinical forms of the disease, and the levels of these transcripts were correlated with the DR and SR. Cardiac patients exhibited lower mRNA expression levels of GATA-3, FoxP3, AHR, IL-4, IL-9, IL-10 and IL-22 but exhibited higher expression of IFN-γ and TNF-α compared with indeterminate patients. Digestive patients showed similar levels of GATA-3, IL-4 and IL-10 than indeterminate patients. Cardiodigestive patients exhibited higher levels of TNF-α compared with indeterminate and digestive patients. Furthermore, we demonstrated that patients with high DR and SR exhibited lower GATA-3, FoxP3, and IL-10 expression and higher IFN-γ, TNF-α and iNOS mRNA expression than patients with low DR and SR. A negative correlation was observed between Foxp3 and IL-10 mRNA expression and the DR and SR. Moreover, TNF-α and iNOS expression was positively correlated with DR and SR. Our data suggest that an inflammatory imbalance in chronic Chagas disease patients is associated with a high DR and SR. This study provides a better understanding of the stroke pathobiology in the general population and might aid the development of therapeutic strategies for controlling the morbidity and mortality of Chagas disease.